Experiences of crisis care among service users with complex emotional needs or a diagnosis of 'personality disorder', and other stakeholders: systematic review and meta-synthesis of the qualitative literature. Issue 2 (24th March 2022) - DeLeo, Kristiana; Maconick, Lucy; McCabe, Rose; Broeckelmann, Eva; Sheridan Rains, Luke; Rowe, Sarah; Johnson, Sonia
Abstract : Background: Mental health crises are common in people with complex emotional needs (our preferred working term for people diagnosed with a 'personality disorder'), yet this population is often dissatisfied with the crisis care they receive. Exploring their experiences and views on what could be improved, and those of carers and healthcare staff, is key to developing better services. Aims: We aimed to synthesise the relevant qualitative literature. Method: Five databases were searched. Eligible studies included service users with a diagnosis of personality disorder and their carers or relevant staff, focused on crisis responses and used a qualitative design. Data were analysed with thematic synthesis. Results: Eleven studies were included, most focusing on emergency departments. Four meta-themes emerged: (a) acceptance and rejection when presenting to crisis care: limited options and lack of involvement of carers; (b) interpersonal processes: importance of the therapeutic relationship and establishing a framework for treatment; (c) managing recovery from a crisis: clear recovery plan and negotiating collaboration; and (d) equipping and supporting staff: training and emotional support. Conclusions: Our findings suggest that emergency departments have major limitations as settings to provide crisis care for people with complex emotional needs, but there is a lack of research exploring alternatives. The quality of the therapeutic relationship was central to how care was experienced, with collaborative and optimistic staff highly valued. Staff reported feeling poorly supported in responding to the needs of this population. Research looking at experiences of a range of care options and how to improve these is needed.